1988
DOI: 10.1002/j.1537-2197.1988.tb13434.x
|View full text |Cite
|
Sign up to set email alerts
|

An Electrophoretic Investigation of Intragametophytic Selfing in Equisetum Arvense

Abstract: Because homosporous pteridophytes (Psilotophyta, Arthrophyta, most Microphyllophyta and Pteridophyta) produce bisexual gametophytes, it was maintained that high levels of inbreeding would characterize these plants. Electrophoretic evidence was used to estimate the frequency of intragametophytic selfing in Equisetum arvense (Arthrophyta). A total of 669 samples from 17 populations was examined from western North America. Although some populations exhibited as many as seven or eight genotypes, 10 populations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Variety protobillotii has higher levels of genetic diversity than var. obovatum, although they are also relatively low (A ϭ 1.3, p ϭ 28.6, H o ϭ 0.014, and H e ϭ 0.014) and are similar to the ones obtained for Botrychium virginianum (L.) Sw. (Soltis and Soltis, 1986), Blechnum spicant (L.) Roth , Equisetum arvense L. (Soltis, Soltis, and Noyes, 1988), and Hemionitis palmata L. (Ranker, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Variety protobillotii has higher levels of genetic diversity than var. obovatum, although they are also relatively low (A ϭ 1.3, p ϭ 28.6, H o ϭ 0.014, and H e ϭ 0.014) and are similar to the ones obtained for Botrychium virginianum (L.) Sw. (Soltis and Soltis, 1986), Blechnum spicant (L.) Roth , Equisetum arvense L. (Soltis, Soltis, and Noyes, 1988), and Hemionitis palmata L. (Ranker, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Electrophoretic analysis of naturally occurring fern populations also revealed diploid gene expression of enzyme-encoding loci (Haufler and Soltis 1984;Gastony and Gottlieb 1985). These findings discrediting the paleopolyploid hypothesis in homosporous ferns were subsequently generalized for the homosporous vascular plants as a whole (Haufler and Soltis 1986;Soltis 1987, 1988a,b;Soltis et al 1988). Thus isozyme studies showed that despite their high chromosome numbers, homosporous ferns with the lowest chromosome number in their genus (n ¼ 27-52) have gene expression patterns typical of diploid angiosperms.…”
mentioning
confidence: 92%
“…Thus the hypothesized high level of self-fertilization in bisexual gametophytes was rejected, and the supposed need for polyploid homoeologous heterozygosity to counteract homologous homozygosity disappeared. These findings discrediting the paleopolyploid hypothesis were subsequently generalized for the homosporous pteridophytes as a whole (3,(14)(15)(16)(17)(18)(19).…”
Section: Resultsmentioning
confidence: 84%